109k views
17 votes
Solve by using the quadratic formula:
x2 - 6x + 7 = 0

User RMcG
by
5.7k points

1 Answer

8 votes

Final Answer:
x = 3 + √(2), 3 - √(2)

Steps/Reasons/Explanation:

Question: Solve by using the quadratic formula:
x^(2) - 6x + 7 = 0.

Step 1: Use the Quadratic Formula.


x = \frac{6 + \sqrt[2]{2} }{2}, \frac{6 - \sqrt[2]{2} }{2}

Step 2: Simplify solutions.


x = 3 + √(2), 3 - √(2)

~I hope I helped you :)~ The quadratic formulaic is attached in an image.

Solve by using the quadratic formula: x2 - 6x + 7 = 0-example-1
User Thomas Klemm
by
5.8k points